Efficient and effective automated surveillance agents using kernel tricks - Ahmed, Tarem; Pathan, Al-Sakib Khan; Ahmed, Supriyo Sabbir; Wei, Xianglin (© 2012 The Society for Modeling and Simulation International., 2016)
This article was published in the SIMULATION [© 2012 The Society for Modeling and Simulation International.] and the definite version is available at: http://doi.org/10.1177/0037549712460908 The Article's website is at: http://sim.sagepub.com/content/89/5/562